Preventable diseases: seminar focus on health complications of early marriage, respiratory distress and vaccinations - Agege, Emmanuel A.; Akuirene, Omatseye A.; Bello, Umar; Moyegbone, John E.; Odoko, Joseph O.; Ahmed, Abdullahi; Abdul-Baqi, Magaji; Garba, Ahmed; Mijinyawa, Ibrahim; Kio, Franklin E.; Esegbue, Peter; Ofili, C. Charles; et al. (International Journal Of Community Medicine And Public Health, 2022)
It is a known fact that preventable diseases are illnesses, or deaths that could be stopped from occurring. As a part of the ongoing Ph.D. program undertaken by the current and pioneer students in the Novena University, Ogume, different research topics were chosen by individual students which were presented as seminar being part of the requirement for the update of their research adventures. The topics were categorized under 3 different groups and one was preventable diseases such as complications of early marriage amongst women, respiratory distress among pregnant women/children and knowledge, attitude and practice of immunization against childhood vaccine preventable diseases among mothers. Complications of early marriage amongst women results in maternal mortality, vesico-vaginal fistula and psychological distress. Gas flaring being environmental pollution exposes women and children to respiratory diseases, hence culminating in maternal and child morbidity and mortality. Furthermore, vaccine preventable diseases are major threats to the health and well-being of children under five years of age, contributing a great deal to childhood illnesses, disabilities, and high percentage of childhood mortality worldwide.